Position of Joint Assets in Marriages that Lead to Divorce (Decision Study No.419/Pdt.G/2021/Pn.Tng) - Andrew Giovanni Tanjaya; Gunawan Djajaputra (Jurnal Hukum Adigama, 2022)
Marriage is a sacred and noble relationship intended for humans in terms of development to continue offspring and spend life with someone we love. Marriage in Indonesia is regulated in Law Number 1 of 1974 concerning Marriage and also the Civil Code. In marriage, assets that have been owned so far will indirectly become joint property since the marriage took place as long as there is no agreement regarding the separation of assets. This study uses a normative juridical method, namely legal research conducted by examining literature or secondary data as the basis for research. The data collection technique is by conducting a literature study of the Law and Decision No.419/Pdt.G/2021/Pn. Tng to find out how the position of joint assets collected during marriage becomes joint property like this when a divorce is in progress. the parties who control the joint property must voluntarily surrender the joint property based on the decision of the marriage agreement made or in accordance with the applicable decision, which can also be done by confiscating the marriage property by the bailiff.